A Review Paper on Intelligent System for Automobile Accident Prevention - Nitnaware, P.T.; Riat, GurpreetSingh; Bajpai, 3Somil (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
There is a problem of road accident which are increasing now a days. So it is the need of time to reduce the accidents by designing a system which saves life of passengers and driver. In the project we provide a means of accident prevention by using eye blink sensor and heart beat sensor wherein the vehicle is stopped immediately